EVOLUTION OF CONCEPT OF CONTROLLING - Otlivanskaya, Natalia (Proceedings of National Aviation University (archive), 2013)
Main prerequisites for development of controlling and its goals are considered. Summary of key concepts that are found in the works of German scientists - the founders of the theory of controlling, is made.